Combination strategies based on epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors for cancer patients: Pooled analysis and subgroup analysis of efficacy and safety. Issue 13 (March 2019) - Xu, Ran; Shao, Hong; Zhu, Jing; Ju, Qianqian; Shi, Hui
Abstract: Background: Combination therapy based on epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) is an emerging trend in cancer treatment, but the clinical value of EGFR-TKIs combination therapy remains controversial. Thus, we conducted a comprehensive analysis of randomized controlled trials (RCTs) comparing EGFR-TKIs combination therapies with monotherapies, aiming to evaluate the safety and efficacy of EGFR-TKIs based combination therapy and to find a more beneficial combination strategy. Methods: We searched for clinical studies that evaluated EGFR-TKIs combination therapy in cancer. We extracted data from these studies to evaluate the relative risk (RR) of overall response rate (ORR) and grade 3/4 treatment-related adverse events (AEs), the hazard ratios (HRs) of overall survival (OS), and progression-free survival (PFS). Results: Fourteen RCTs were identified (n = 3774). Treatments included combinations of EGFR-TKIs and chemotherapy, combinations of EGFR-TKIs and radiotherapy, and combinations of EGFR-TKIs and bevacizumab. EGFR-TKIs combination therapies showed higher ORR [RR: 1.62; 95% confidence interval (95% CI):1.16–2.26; P = .005], PFS (HR: 0.76; 95% CI: 0.64–0.89; P = .001), and OS (HR: 0.88; 95% CI: 0.79–0.97; P = .013) values than monotherapies. However, higher grade 3/4 treatment-related AEs (RR: 1.79; 95% CI: 1.02–3.15; P = .000) were observed in combination therapy than in monotherapy. Conclusion: Our pooled analysis and subgroup analysis results showed that the addition of chemotherapy to EGFR-TKIs better benefits PFS and safety. Adding bevacizumab was associated with better ORR and OS. The efficacy and safety of a bevacizumab-EGFR-TKIs-chemotherapy combination should be investigated further. Abstract : Supplemental Digital Content is available in the text